The Investigation into Pronunciation Problems Faced by Teacher-Trainees: A Case Study at the National Institute of Education (NIE) in Cambodia - Moeung Phany; Doung Dara (Indonesian Journal of Advanced Research, 2024)
This study investigates pronunciation challenges among English major -students at National Institute of Education, focusing on segmental and supra-segmental pronunciation issues, contributing factors, and potential remediation strategies. The study employed qualitative approach utilizing research apparatuses adjusted from previous studies. Additionally, ten teacher trainees with at least six years of English language learning background consented to participate in this study, while four lecturers were also incorporated. The findings were identified primarily with labiodental, dental, velar, alveolar, and palatal consonants, and with the monophthong sounds /i:/ and /ɒ/, and diphthongs /eɪ/ and /ɪə/. Factors influencing pronunciation proficiency include inadequate qualified teachers, insufficiently structured language programs, first language interference, and limited access to learning resources, alongside motivational and environmental factors, age, and beliefs. Recommendations for improvement emphasize integrating technology and social media for accessing pronunciation tutorials, extending instructional hours, and encouraging regular English-speaking practices.